2023
DOI: 10.26434/chemrxiv-2023-k7mws
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling of enhanced water flow in deformable carbon nanotubes using a linear pressure-diameter relationship

Ashish Garg

Abstract: Numerous researchers have documented a notable enhancement in water flow through nanotubes While modelling, these researchers typically treated the CNTs with rigid walls. The flow rates of water within carbon nanotubes (CNTs) are significantly influenced by the nanoconfined density, viscosity and the slip length. Despite considering substantial slip effects, there are unresolved findings of massive enhancements in flow rates. Recently, using a linear pressure-area relationship for the deformable tube walls, Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Also, during the production of impact absorbing fabric materials, the shear-thickening fluids (which are the combination of the Newtonian, power-law shear thinning and shear thickening fluid depending on the applied shear rate) flow in such porous geometries [12,13]. In addition, the flow happens through the corrugated nanochannels or nanotubes for the biopolymer filtration processes [14][15][16]. Research on the flow of non-Newtonian fluids in corrugated channels has shown that the flow recirculation formed in the valley of the corrugations enhances heat transfer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, during the production of impact absorbing fabric materials, the shear-thickening fluids (which are the combination of the Newtonian, power-law shear thinning and shear thickening fluid depending on the applied shear rate) flow in such porous geometries [12,13]. In addition, the flow happens through the corrugated nanochannels or nanotubes for the biopolymer filtration processes [14][15][16]. Research on the flow of non-Newtonian fluids in corrugated channels has shown that the flow recirculation formed in the valley of the corrugations enhances heat transfer [17].…”
Section: Introductionmentioning
confidence: 99%
“…The recent surge in nanoscale technology has ignited significant interest in understanding fluid flow within these confined environments [1][2][3][4][5][6][7]. This interest stems from the unique behavior exhibited by fluids at the nanoscale, where fundamental assumptions like uniform density, noslip boundaries, and even the validity of the Navier-Stokes equations, become questionable [6].…”
Section: Introductionmentioning
confidence: 99%